2007
DOI: 10.1360/yc-007-0047
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the relationship between sow maternal behav-iour during early lactation and polymorphism of PRLR gene

Abstract: PCR-RFLP technique was applied to analyze single nucleotide polymorphisms of PRLR gene in Minpig and Landrace to investigate the possible effect of PRLR gene on sow maternal behaviour. A Nae I-RFLP site was detected in the PRLP gene. The single nucleotide polymorphism, a T-->C transition at nucleotide 1,620 of the cDNA sequence, was a silent mutation. Least square analysis between the genotypes and the maternal behavioural traits showed that sows with genotype AB had a significantly higher frequency of lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Significant attention has focused on the potential use of the PRLR gene as a marker for reproductive performance in several mammalian species. Recently, it was reported that PRLR plays an essential role in the induction of the maternal behavior (Lucas et al, 1998;Kelly et al, 2001;Baran et al, 2002;Tomás et al, 2006;Cui et al, 2007;Chen et al, 2010). These results clearly establish PRLR as a regulator of maternal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Significant attention has focused on the potential use of the PRLR gene as a marker for reproductive performance in several mammalian species. Recently, it was reported that PRLR plays an essential role in the induction of the maternal behavior (Lucas et al, 1998;Kelly et al, 2001;Baran et al, 2002;Tomás et al, 2006;Cui et al, 2007;Chen et al, 2010). These results clearly establish PRLR as a regulator of maternal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…High amino acid variability within the intracellular domain of porcine PRLR has been reported in association with differences in the number of corpus lutea of sows, and the preweaning survivability of piglets (Tomás et al, 2006). The PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) technique was applied to analyze single nucleotide polymorphisms (SNPs) of PRLR exon 10 in Minipig and Landrace breeds, to investigate the possible effect of PRLR on sow maternal behavior (Cui et al, 2007). An NaeI-RFLP site was detected and three genotypes were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for associations between gene and maternal behavior has been reported (Tanaka, 2002;Tomás et al, 2006;Nishimori et al, 2008;Mileva-Seitz et al, 2012;Avinun et al, 2012); these findings have advanced our understanding of the genetic influences on maternal behavior. It has been reported that PRLR plays an essential role in the induction of the maternal behavior (Lucas et al, 1998;Cui et al, 2007;Chen et al, 2010a). These results clearly establish PRLR as a regulator of maternal behavior.…”
Section: Introductionmentioning
confidence: 99%